A comprehensive comparison and analysis of soil screening values derived and used in China and the UK. (January 2020) - Sun, Yiming; Wang, Jicai; Guo, Guanlin; Li, Hong; Jones, Kevin
Abstract: China and the UK use different risk-based approaches to derive soil screening or guideline values (SSVs; SGVs) for contaminants. Here we compare the approaches and the derived values for 6 illustrative contaminants. China's SSVs are derived using an approach developed in the US as follows: for carcinogens, acceptable level of risk (ACR) is set at 10 −6 and the SSVs calculated as 10 −6 divided by the soil exposure and toxicity data; for non-carcinogens, the hazard quotient is 1 and the SSV is calculated as 1 divided by the soil exposure and toxicity data. The UK's SGVs are calculated by the CLEA model, for which the Average Daily Exposure (ADE) from soil sources by a specific exposure route equals the health criteria values (HCVs) for that route, whether for carcinogens or a non-carcinogens. The UK's CLEA model is also used here to derive SSVs with Chinese input parameters. China's SSVs, the UK's SGVs and values for Chinese conditions derived using the UK approach were as follows (mg/kg): As, <1, 35, 20; Cd, 20, 18, 11; Cr (VI), <1, 14, 29; benzene, 1, 1, 2; toluene, 1200, 3005, 3800; ethyl-benzene, 7, 930, 1200. By comparing the differences in toxicity assessment and risk characterization, exposure assessment and parameter types in the methodologies to obtain SSVs in China and the UK, and by combining the CLEA model with Chinese parameterisation, these comparisons highlight that the difference in toxicity assessment and risk characterization methods of carcinogens results in the biggest difference in SSVs between the 2 countries. However, for non-carcinogenic substances, the difference of SSVs calculation method and SSVs is small. The difference in SSVs for carcinogenic substances is also related to the route of exposure. For volatile organic compounds, the presence of indoor respiratory exposure pathways greatly reduces the differences caused by toxicity assessment and risk characterization methods. For non-volatile substances such as heavy metals, the effects of toxicity assessment and risk characterization methods are significant. The SSV of As obtained by the CLEA model with Chinese parameters is closer to the background value of soil in China. In the management of non-volatile contaminated sites such as heavy metals in China, the CLEA model can be used for risk assessment and calculation of site specific SSVs. In the future, China can use the UK method to strengthen its toxicity assessment and risk characterization methods for carcinogenic substances, to reduce the uncertainty in the risk assessment of contaminated sites and improve the scientific management of contaminated sites. Graphical abstract: Image 1 Highlights: China and UK approaches to derive soil screening values (SSVs) are compared. Results for carcinogens show the biggest difference in SSVs between countries. For non-carcinogenic substances the difference in SSVs is small. China can improve risk assessment and management of brownfield sites. Abstract : Improvements are suggested to derive China's national soil screening values.